1999
DOI: 10.1161/01.hyp.33.2.698
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen Gene Polymorphisms M235T/T174M

Abstract: Abstract-The gene encoding angiotensinogen (AGT) has been widely studied as a candidate gene for hypertension. Most studies to date have relied on case-control analysis to test for an excess of AGT variants among hypertensive cases compared with normotensive controls. However, with this design, nothing guarantees that a positive finding is due to actual allelic association as opposed to an inappropriate control population. To avoid this difficulty in our study of essential hypertension in Anqing, China, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…the RAS may be the most important of the endocrine system that affects the control of blood pressure (16,19). Some studies reported a possible influence of polymorphisms of genes encoding for components of the RAS such as the angiotensinogen (AGt) (30,33), the angiotensin converting enzyme (Ace) (10,28), and the angiotensin ii type 1 receptor (AtiR) on the onset of hypertension (15,38), while others did not (26,27,34). one frequently studied gene has been AGt, a logical candidate gene, given the strong correlation of plasma AGt levels and blood pressure (2,14).…”
Section: Introductionmentioning
confidence: 99%
“…the RAS may be the most important of the endocrine system that affects the control of blood pressure (16,19). Some studies reported a possible influence of polymorphisms of genes encoding for components of the RAS such as the angiotensinogen (AGt) (30,33), the angiotensin converting enzyme (Ace) (10,28), and the angiotensin ii type 1 receptor (AtiR) on the onset of hypertension (15,38), while others did not (26,27,34). one frequently studied gene has been AGt, a logical candidate gene, given the strong correlation of plasma AGt levels and blood pressure (2,14).…”
Section: Introductionmentioning
confidence: 99%
“…Se han llevado a cabo numerosos estudios genéticos sobre estos sistemas; sin embargo, los resultados han sido incongruentes entre poblaciones, lo que evidencia la heterogeneidad de la hipertensión arterial en su etiología genética en las poblaciones continentales (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58).…”
unclassified
“…Among the 22 eligible articles, a study by Chiang et al 34 was replaced with a later report 21 that included a larger population. Moreover, Fang et al 35 and Niu et al [36][37][38] were excluded as they were family-based studies. In addition, the genotype data of the control population provided in He et al 39 was excluded, as it deviated from HWE (P HWE o0.0001).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%